Capabilities of Entrepreneurs in the Execution of Strategies in SSIs in two States of India: A Comparative Study - Kar, Bibhu Prasad; Kalyani, Muna; Borah, Sourav Bikash (Prabandhan: Indian Journal of Management, 2012)
Purpose: Gujarat and Odisha are two different provinces in the Indian sub-continent under the South-Asiatic region. Gujarat, with less mineral resources, tribal population and moderate poverty prospered economically due to the setting up of new industries, particularly in the Small Scale Sector (SSI). On the other hand, Odisha, inspite of its vast natural resources like minerals, forests, rivers, population, long coast line, natural harbours and surplus electricity has all characteristics of poverty. This phenomenon led to an approach. Approach: Both the states are similar in many ways, yet the people of Odisha live under abject poverty. Small Scale Industries (SSIs) flourish in Gujarat but become sick in Odisha. Causes to these aspects draw serious attention of the people of Odisha. A study was initiated in this context to find out the drawbacks of poor performance of the state in the SSIs sector. The prosperity of Gujarat SSIs have been described through the management of seven major social & financial factors. Strategy-activities of SSIs of Gujarat and Odisha have been compared and the differences are brought out for the entrepreneurs of Odisha to consider and follow for the high growth of the SSEs in the state. Findings: The study reveals that a careful execution of strategy with a prudent use of the state's natural, social and financial resources made Gujarat Small Scale Enterprises (SSEs) more advantageous for high economic growth, which was not observed in the case of Odisha SSEs.